HLH-30/TFEB modulates autophagy to improve proteostasis in Aβ transgenic Caenorhabditis elegans - Lin, Hongru; Zhang, Chen; Gao, Yehui; Zhou, Yi; Ma, Botian; Jiang, Jinyun; Long, Xue; Yimamu, Nuerziya; Zhong, Kaixin; Li, Yingzi; Cui, Xianghuan; Wang, Hongbing (Frontiers in Pharmacology, 2024)
Alzheimer’s disease (AD) is a complex neurodegenerative disease that affects elderly individuals, characterized by senile plaques formed by extracellular amyloid beta (Aβ). Autophagy dysfunction is a manifestation of protein homeostasis imbalance in patients with AD, but its relationship with Aβ remains unclear. Here, we showed that in Aβ transgenic Caenorhabditis elegans, Aβ activated the TOR pathway and reduced the nuclear entry of HLH-30, leading to autophagy dysfunction characterized by autophagosome accumulation. Then, utilizing RNA-seq, we investigated the regulatory mechanisms by which HLH-30 modulates autophagy in C. elegans. We found that HLH-30 elevated the transcript levels of v-ATPase and cathepsin, thus enhancing lysosomal activity. This led to an increase in autophagic flux, facilitating more pronounced degradation of Aβ. Moreover, HLH-30 reduced the level of ROS induction by Aβ and enhanced the antioxidant stress capacity of the worms through the gsto-1 gene. Additionally, we identified two HLH-30/TFEB activators, saikosaponin B2 and hypericin, that improved autophagic flux, thereby enhancing protein homeostasis in C. elegans. Overall, our findings suggested that HLH-30/TFEB plays a key role in modulating autophagy and can be considered a promising drug target for AD treatments.